KINERJA BANK: PENGARUH LAPORAN KEBERLANJUTAN, KUALITAS LABA, DAN MODAL INTELEKTUAL - Putri Hulu, I’is Intan; Utami, Wiwik (Center for Economic Studies Universitas Katolik Parahyangan, 2023)
This study aims to examine the effect of the quality of sustainability reports and earnings quality on bank performance as a proxy for return on assets and price earnings ratio with intellectual capital as a moderating variable. The population of this study were banking companies listed on the IDX for 2018-2021 with a total of 46 companies. Determining the number of samples was carried out using a purposive sampling technique and selected based on criteria of 28 companies for a period of 4 years so that 112 samples were obtained. Regression analysis method on panel data using the Eviews 12 program. The results of this study indicate that the quality of sustainability reports has a significant negative effect on ROA. Earnings quality has a positive and significant effect on ROA. Report quality has a positive and significant effect on PER. Earnings quality has no significant effect on PER. ROA has a positive and significant effect on PER. Intellectual capital is able to moderate the influence of the quality of sustainability reports on PER. Intellectual capital cannot moderate the effect of sustainable earnings quality on PER. Intellectual capital cannot moderate the effect of ROA on PER